Surges - Qureshi, Mahvash (IMF Working Papers; Working Paper, 2012)
This paper examines why surges in capital flows to emerging market economies (EMEs) occur, and what determines the allocation of capital across countries during such surge episodes. We use two different methodologies to identify surges in EMEs over 1980-2009, differentiating between those mainly caused by changes in the country's external liabilities (reflecting the investment decisions of foreigners), and those caused by changes in its assets (reflecting the decisions of residents). Global factors-including US interest rates and risk aversion are key to determining whether a surge will occur, but domestic factors such as the country's external financing needs (as implied by an intertemporal optimizing model of the current account) and structural characteristics also matter, which explains why not all EMEs experience surges. Conditional on a surge occurring, moreover, the magnitude of the capital inflow depends largely on domestic factors including the country's external financing needs, and the exchange rate regime. Finally, while similar factors explain asset- and liability-driven surges, the latter are more sensitive to global factors and contagion.